Does ICT affect the understanding of ellipsoids, cylinders and cones among students from University of Applied Sciences?. (2018) - Zaranis, Nicholas; Exarchakos, George M.
Our research compares the improvement of the students' stereometry competence of ellipsoids, cylinders and cones using two teaching approaches. The first one employs our ICT-oriented learning method specifically targeting the Van Hiele model for stereometry concepts. The second method is based on the traditional approach of teaching university students. The study deals with second year undergraduate students form the Department of Civil Engineering at Piraeus University of Applied Sciences. The sample was divided into two groups (experimental and control). The results showed that the teaching approaches of our intervention, with the additional use of ICT using the background of the Van Hiele model, contribute significantly more to the development of university students' stereometry competence as compared to other traditional methods.